The Influence of Kinetic Sand Media on the Fine Motor Development of Children Aged 4-5 Years at Immanuel Kids Kindergarten FY 2022/2023 - Jelita Esteria Marpaung; Dorlince Simatupang (PT FORMOSA CENDEKIA GLOBAL, 2023)
The aim of this research is to see the effect of kinetic sand media on the fine motor development of children aged 4-5 years for FY 2022/2023, the population in this research consists of three classes in Kindergarten A, the sampling technique uses random sampling, namely 20 people. The type of research is Quasi-Experimental, using non-parametric statistics. The results of the research show that the fine motor skills of children aged 4-5 years in the domain of forming, printing, grasping and hand-eye coordination activities increase using kinetic sand media in the experimental class compared to using other media. playdough in the control class. This can be seen from the average value in the experimental class of 13.70, maximum value 16, minimum value 11 while in the control class the average value is 11.50, maximum value 16, minimum value 8 where the test results are different samples kolmogorov smirnov. Based on the hypothesis test shows that, it can be seen that the p-value or Asymp. Sig = 0.164 > 0.05. That is, H0 is rejected and Ha is accepted. Thus, it can be concluded that there is a significant influence of the use of kinetic sand media on the fine motor development of children aged 4-5 years at Immanuel Kids Amplas Kindergarten FY 2022/2023.